2022
DOI: 10.1055/a-1577-8663
|View full text |Cite
|
Sign up to set email alerts
|

Arterielle Hypertonie – Eine Übersicht für den ärztlichen Alltag

Abstract: Die immense Bedeutung des Bluthochdrucks erwächst nicht nur aus der Häufigkeit der Erkrankung, sondern besonders aus dem mit der Erkrankung einhergehenden erhöhten kardiovaskulären Risiko. Bis zu 10 Millionen Todesfälle pro Jahr gehen weltweit auf erhöhten Blutdruck zurück. Diese Übersicht über die möglichen Ursachen, Diagnostik und leitliniengerechte Therapie soll helfen, die Versorgung von Patienten mit arterieller Hypertonie zu verbessern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…HT affects more than one quarter of the world's population. Globally, more than 1 billion people are believed to have hypertension (2). Its prevalence is also quite high in our country, at 31.8% (3).…”
Section: Introductionmentioning
confidence: 94%
“…HT affects more than one quarter of the world's population. Globally, more than 1 billion people are believed to have hypertension (2). Its prevalence is also quite high in our country, at 31.8% (3).…”
Section: Introductionmentioning
confidence: 94%
“…Hypertension is a common chronic disease with high prevalence and is one of the most prevalent risk elements for cardiovascular disease (CVD) ( 1 , 2 ). According to epidemiologic statistics, there are approximately 1 billion hypertensive patients worldwide, and it is projected that the population of hypertensive patients will increase to 1.292 billion by 2025 ( 3 , 4 ). In the United States, it was found that the prevalence of hypertension in adults is about 32%–46% ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, researchers used estimated pulse wave velocity (ePWV) to assess the degree of aortic stiffness using an algorithm including age and mean blood pressure (MBP) [10]. At present, ePWV is considered an alternative to cfPWV [11], which may have critical importance in forecasting morbidity and mortality of people with obesity with different complications [12]. In this study, we analyzed the correlation between e-PWV and mortality in patients with obesity.…”
Section: Introductionmentioning
confidence: 99%